2003
DOI: 10.1093/ndt/18.2.318
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of heart rate variability in patients with end-stage renal disease on chronic haemodialysis

Abstract: Decreases in some HRV measures, particularly those reflecting long-term variability, are independent predictors of cardiac death in chronic haemodialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
125
2
9

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(140 citation statements)
references
References 20 publications
4
125
2
9
Order By: Relevance
“…We previously reported that reduced HRVTI and ULF were independent predictors of cardiac death in hemodialysis patients (3,4), but the number of events was insufficient as convincing evidence (24). Oikawa et al (5) conducted a 5.8-year prospective study of 383 hemodialysis patients and found that SDNN ,75 ms independently predicted all-cause and cardiovascular mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that reduced HRVTI and ULF were independent predictors of cardiac death in hemodialysis patients (3,4), but the number of events was insufficient as convincing evidence (24). Oikawa et al (5) conducted a 5.8-year prospective study of 383 hemodialysis patients and found that SDNN ,75 ms independently predicted all-cause and cardiovascular mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of heart rate variability (HRV) by 24-hour electrocardiography has become a noninvasive tool for risk stratification in various clinical settings, including hemodialysis patients (2)(3)(4)(5). Conventionally, two categories of measures have been used: time-domain HRV measures calculated as statistics of R-R intervals and frequency-domain HRV measures computed by spectrum analysis as R-R interval variances within specific frequency bands (6).…”
Section: Introductionmentioning
confidence: 99%
“…Lower HRV has a significant predictive value for various CVDs, such as ventricular arrhythmias and sudden death (13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…3,12,17,18 The HRV reduction in patients with CKD is considered a risk factor for the occurrence of cardiac arrhythmias, and is associated with a higher cardiovascular mortality. 4,5 Cashion et al 19 , assessing hemodialysis patients by use of 24-hour Holter to study HRV in the time and frequency domains for a period of two years, have reported that the reduction in the SDNN, LF, and LF/HF parameters predicted cardiovascular death, especially sudden death. In that population, the reduction in HRV associated with injury to the parasympathetic system due to the structural impairment of arteries or the functional alterations of the autonomic nervous system secondary to uremic toxins.…”
Section: Discussionmentioning
confidence: 99%
“…3 In addition, the reduction in HRV represents an independent risk factor for cardiac mortality in those patients. 4,5 Thus, strategies, such as exercise training, have been implemented aiming at reducing cardiovascular mortality due to an increase in HRV and improvement of the left ventricular function, specially in the population with heart disease. 6,7 However, only a few studies have assessed the effect of an exercise training program on those cardiovascular parameters in patients with CKD undergoing hemodialysis.…”
Section: Introductionmentioning
confidence: 99%